Are powerful presidents always popularly elected? Implications for separating semi-presidentialism from parliamentarism. Issue 2 (17th February 2019) - Anckar, Carsten
ABSTRACT: The traditional conception of semi-presidentialism stipulates that powers are shared by a popularly elected president and a prime minister, who is responsible to parliament. In recent years, an increasingly popular strategy has become to disregard the power dimension and define semi-presidentialism only with regard to whether the president is popularly elected or not. Based on a principal-agent framework the present study sets out to test the relationship between the mode of election and the powers of the president in democratic republics where the government is dependent on the legislature for survival. Findings indicate that although powerful presidents most often are popularly elected there are also instances where a non-popularly elected president shares executive powers with the prime minister. This makes it difficult to define semi-presidentialism only with regard to how the president comes to power.